2017
DOI: 10.1021/acs.jpclett.7b01335
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Structures of the Active Sites Responsible for the Improved Reduction of Carbon Dioxide by Gold Nanoparticles

Abstract: Gold (Au) nanoparticles (NPs) are known experimentally to reduce carbon dioxide (CO 2 ) to carbon monoxide (CO), with far superior performance to Au foils. To obtain guidance in designing improved CO 2 catalysts, we want to understand the nature of the active sites on Au NPs. Here, we employed multiscale atomistic simulations to computationally synthesize and characterize a 10 nm thick Au NP on a carbon nanotube (CNT) support, and then we located active sites from quantum mechanics (QM) calculations on 269 ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 23 publications
3
50
0
Order By: Relevance
“…The scientific research can be more comprehensive compared with the complicated solvation model, especially for the system-atical studies on some variable and high-throughput screening of a series of materials. These results qualitatively reproduced experimental observations that (211) surfaces required lower applied potentials than (111) and (100) Reproduced with permission. [32] They examined (111), (100), and (211) surfaces, and found enhanced intermediate stabilization and lower onset potentials for CH 4 evolution on (211) surfaces, whereas the close-packed surfaces (111) and (100) are less active.…”
Section: Che Modelsupporting
confidence: 85%
See 3 more Smart Citations
“…The scientific research can be more comprehensive compared with the complicated solvation model, especially for the system-atical studies on some variable and high-throughput screening of a series of materials. These results qualitatively reproduced experimental observations that (211) surfaces required lower applied potentials than (111) and (100) Reproduced with permission. [32] They examined (111), (100), and (211) surfaces, and found enhanced intermediate stabilization and lower onset potentials for CH 4 evolution on (211) surfaces, whereas the close-packed surfaces (111) and (100) are less active.…”
Section: Che Modelsupporting
confidence: 85%
“…[32] They examined (111), (100), and (211) surfaces, and found enhanced intermediate stabilization and lower onset potentials for CH 4 evolution on (211) surfaces, whereas the close-packed surfaces (111) and (100) are less active. The scientific research can be more comprehensive compared with the complicated solvation model, especially for the system-atical studies on some variable and high-throughput screening of a series of materials.…”
Section: Che Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5]7,12,14,15] Since the study showing a linear correlation between grain boundary (GB) density and CO 2 RR performance by Li et al, [16] GBs have been explored as highly active catalytic sites for both CO 2 RR and carbon monoxide reduction, which promoted the production of CO and formic acid. [18] Hence it would be interesting to realize Cu nanostructures with high TB for CO 2 RR. [17] Cheng et al also reported a theoretical study showing that highly active twin boundaries (TBs) on the Au surface can be superior to GBs and other defects for CO 2 RR.…”
Section: Doi: 101002/adma201805405mentioning
confidence: 99%